TINJAUAN FIKIH MAWARIS TERHADAP PEMBAGIAN HARTA WARIS BERDASARKAN HUKUM ADAT GAYO DI WILAYAH DESA TETINGI KECAMATAN BLANGPEGAYON KABUPATEN GAYO LUES - Saripudin; Syamsuddin; Baehaqi (JAS : Jurnal Ahwal Syakhshiyyah, 2023)
This study aims to explain the fiqh Mawaris review of the distribution of inheritance based on Gayo customary law in the area of Tetingi Village, Blangpegayon District, Gayo Lues Regency. And explained about Gayo customary inheritance in Tetingi village. In this case the research subject is the Tetingi village community, while the object of study is Islamic views using qualitative methods.  The results of the study, the authors concluded that the inheritance system in Tetingi Village, Blangpegayon District, Gayo Lues Regency still uses patrilineal principles, namely a hereditary system that draws a line of descent where a man's position is more prominent and only connects himself to his father over his father and so on or descendants of ancestors. male in inheritance. Gayo's customary system which is called inget urum set (customs and regulations) has become a hereditary tradition. After Islam came and developed, adat took the form of inget urum atur (customs and regulations), changing the term to edet urum ukum (adat with Islamic law). Because Islamic law is accepted by customary law and accepted by the Gayo indigenous people in the village of Tetingi. Then the term Gayo appears in it " Hukum urum edet , song zet urum sifet " which means the relationship between Islamic law and Gayo adat , such as substance and nature.The division of inheritance based on Gayo customary law remembers the general rules (customs and regulations) in the village of Tetingi, when viewed from the jurisprudence of the Mawaris/Islamic law it is not contradictory because the Islamic inheritance law/fikih Mawaris has been accepted by the Gayo customary inheritance system and accepted by the Gayo indigenous people in the village so that it becomes edet urum ukum (adat with Islamic law). So that in its application it is in accordance with or in line with the provisions of Islamic law. Keywords: Gayo Tribe Customs, Inheritance , Traditional Inheritance, Fiqh Mawaris